A SMALL COUNTRY, A SMALL PUBLISHING HOUSE: THE CASE OF ARTSERIA - ZOVIENĖ, DANUTĖ (Knygotyra, 2014)
The article analyses a case study of artseria, a publisher of the Lithuanian Artists’ Association, with the goal of analysing the situation of a small participant of the Lithuanian book publishing and bookselling in terms of financial sources and demand group of specialized literature. The problems encountered by artseria and other small publishers are approached from the historical and statistical aspects as well as commercial perspective. The article has used the data provided by the Lithuanian Statistics Department, the bulletin Lietuvos spaudos statistika 2012 [Statistics of Lithuanian Press 2012], reports by UAB Creditreform Lietuva and other documents. The Lithuanian publishers, especially small ones, have to cope with two major challenges, those of securing resources for book publishing and selling of their production. Creative problems related to book content, book production and printing quality are no longer an issue, though there have been different times during the 23 years of independence. In contrast to Western countries, Lithuanian publishers do not specialize in the strict sense, most of them produce books across a range of themes. This situation is caused by the type of the local market and strong competition for broadened readership. The artseria stands out among other Lithuanian publishers by its ambitious goal to keep to the established repertoire, with the focus on the aesthetics and the art of the book. The collection by the publisher is composed of publications dedicated to professional art of the 20th–21st century Lithuanian art, Dailė [Art] magazine published semi-annually, art folio publications, monographs dedicated to Lithuanian artists and exhibition catalogues. With over 15 years of work under its belt, artseria has developed a strategy for securing financial resources. It explores all the avenues of support through a range of programmes run by the Ministry of Culture, the Ministry of Education and Science and the Press, Radio and Television Support Fund (SRTRF), applying for grants under the Culture and Publications Programme by the Fund. Though artseria is not among the leaders enjoying the biggest financing under the programme, Dailė ranks, in the reports developed by the Fund, among the most valuable Lithuanian cultural periodicals, such as Kultūros barai, Šiaurės Atėnai, Krantai, Lietuvos fotografija, Archiforma and Teatro scena. Lithuanian book market is desperate for changes: it is waiting for a stronger legislative foundation and taxing policy, for revisiting of criteria applied to state financing of publishing and grant allocation, for closer cooperation between publishers and bookselling, for legal regulation of the monopoly policy in bookselling – and above all, for harnessing of unemployment and emigration, so that books may have their readership.